Deep learning outperformed 136 of 157 dermatologists in a head-to-head dermoscopic melanoma image classification task - Brinker, Titus Josef; Enk, Alexander; Kalle, Christof von (European journal of cancer, 2019)
Recent studies have successfully demonstrated the use of deep-learning algorithms for dermatologist-level classification of suspicious lesions by the use of excessive proprietary image databases and limited numbers of dermatologists. For the first time, the performance of a deep-learning algorithm trained by open-source images exclusively is compared to a large number of dermatologists covering all levels within the clinical hierarchy.
Gesehen am 15.10.2019